The Role of Social Media in Increasing Political Literacy of Beginning Voters - Satria M, Deddy; Zulfadli, Zulfadli; Zuhri, Al (Master Program of Sociology, Universitas Malikussaleh, 2023)
Social media has been a significant influence in moulding young voters' political knowledge and engagement, hence improving their political literacy. This study aims to determine social media's role in increasing young voters' political literacy. The method used in this study is a literature review. The stages used in the literature review are article collection, reduction, display, organizing and discussing, and drawing conclusions. This study showed that social media has become a new domain for voters, especially first-time voters with competing candidate pairs. First, social media's role in political literacy is as an agent for disseminating information about political processes and development policies. Second, they become agents of accentuating views, opinions and even people's attitudes towards certain political phenomena. Third, social media is a public space for free discussion and political literacy. Fourth, social media has contributed to the promotion of democracy by carrying out the function of social control, for example the E-KTP corruption case.